FSP synthesized core-shell CuOx@SiO2 catalyst with excellent thermal stability for catalytic combustion of ammonia. (15th February 2023) - Zhou, Guangzhao; Zhang, Yiran; Zhao, Xuteng; Gui, Yu; Wang, Xiaochao; Li, Linjia; Chen, Ting; Huang, Zhen; Lin, He
Highlights: The CuOx @SiO2 catalyst with excellent performance by the FSP method. The CuOx @SiO2 catalyst has good thermal stability due to strong sintering resistance. Catalytic ammonia oxidation over the CuOx @SiO2 catalyst follows fast i-SCR mechanism. Reaction path at low temperature is different from that at high temperature. Abstract: Ammonia has a great application prospect to reach zero-carbon emissions in the combustion society. However, the poor ignition and combustion performance and NOx emissions of ammonia limit its utilization, and catalytic combustion may be a reliable way to utilize ammonia. In this study, the catalysts were prepared by the flame spray pyrolysis method (FSP), and the catalytic combustion performance of ammonia was investigated in a wide temperature range (100–1000 °C). The results indicated that CuOx and core–shell CuOx @SiO2 had high catalytic activity and N2 selectivity under different equivalence ratios compared with other catalysts (FeOx and MnOx ), and the thermal stability of CuOx @SiO2 were more prominent. These two catalysts before and after ammonia catalytic combustion tests were characterized to reveal their acting mechanism. At low temperature (<600 °C), the catalytic ammonia combustion over CuOx followed the internal-selective catalytic reduction (i-SCR) mechanism, while that on CuOx @SiO2 followed the fast i-SCR mechanism, resulting in the outstanding N2 selectivity of CuOx @SiO2 . At high temperature (600–1000 °C), CuOx @SiO2 with a better thermal stability hardly sintered. Hydrogen was generated at high temperature and then reacted with oxygen under low equivalence ratio or with the lattice oxygen of the fresh catalyst under high equivalence ratio. The core–shell CuOx @SiO2 catalyst synthesized by the FSP method provides a novel idea on the catalyst design for catalytic ammonia combustion.